Investigation of factors influencing submarining mitigation with child booster seats. (2nd January 2023) - Forman, Jason; Miller, Matthew; Perez-Rapela, Daniel; Gepner, Bronislaw; Edwards, Marcy A.; Jermakian, Jessica S.
Abstract: Objective: Automobile booster seats are intended to improve belt fit for children that are too large for a harness-style child restraint, but not yet big enough to fit properly in an adult seat belt. Our objective was to prospectively study the relationship between booster seat design and interaction with the seat belt (specifically, submarining risk) for a child occupant using computer simulation of automobile crash events. Methods: Frontal-impact simulations were performed with a 6-year-old child human body model. Simplified models of booster seats were developed using an automated process designed to capture key characteristics of booster geometry, stiffness, belt guide construction, and attachment to the vehicle seat. The child model was positioned in a range of postures from upright to slouched. Our main interest was submarining, where the child's pelvis slips under the lap belt and the belt loads into the abdomen (defined based on the motion of the lower lap belt edge relative to the ASIS). Results: Among the parameters studied, the factors that had the greatest effect on submarining risk were the booster's stiffness and the child's posture. Booster models of a low-stiffness construction (similar to an inflatable booster) nearly always resulted in submarining, regardless of the other design characteristics of the booster. A slouched posture also substantially increased the likelihood of submarining (even for high-stiffness boosters). Conclusions: These results suggest that booster seats of a stiffer construction, and booster seats that promote an upright posture may provide a protective benefit compared to softer boosters and boosters that are more likely to result in slouching of the child.